A BEM/FEM formulation for the analysis of piles submitted to horizontal loads. (August 2017) - Luamba, Endi Samba; Paiva, João Batista de
Abstract: In this paper a coupled Boundary Element Method (BEM)/Finite Element Method (FEM) formulation for the analysis of pile–soil interaction problems with the pile submitted to horizontal loading is presented. The soil is supposed to be a semi-infinite elastic, isotropic continuum and is modeled by the BEM and the piles are modeled by the finite element method. In the final system of equations the unknowns' vector are the displacements and rotations at the nodes of the pile which, unlike other formulations, allows coupling with a foundation plate and a pile cap. Examples of single piles subjected to horizontal loading are analyzed with the presented formulation and their results compared with those from other formulations.